(untitled) (Baghdad Science Journal, 2009)
A study were conducted to examinate the effect of organic and aqueous (Hot, Cold) Extracts from leaves of Duranta repens on the growth and activities of the following types of Bacteria:- Staphylococcus aureus,Streptococcus pyogens ,Escherichia coli,Klebsilla pneumonia, in addition to the yeast Candida albicans and the fungi Aspergullis niger ,Aspergulls flavus.The result showed that gram Positive Bacteria is more sensitive to the extracts than gram negative bacteria with Minimum inhibitory concentration (MIC) value (50,25,50,100)% and Minimum Bactericidal Concentration (MBC) value (100,50,200,100)% for all types Bacteria respectively . The most active extract against A.niger ,A,flavus was cold and hot aqueous extract from the leaves with diameter growth of colony value of ( 0.93,0.37)cm for A.niger in 20 % concentration compared with organic extract (0.26)cm, and the inhibition zone value of cold and hot extract to A.flavus (0.90,0.80)cm respectively compared with organic extract (7.056)cm.